Allelopathic activity of rhizosphere soil in alfalfa - Sorghum sp. mixed growing - Golubinova, Irena; Serafimov, Plamen Marinov; Vasileva, Viliana (The Indian Journal of Agricultural Sciences, 2020)
The allelopathic activity of soil from rhizosphere zone of alfalfa (Medicago sativa L.) grown under cover of Sorghum bicolor L. Sorghum sudanense Piper Staf. and Sorghum vulgare var. technicum Korn. on the initial development of Lactuca sativa L. was assessed. The experiment was performed under laboratory conditions at the Institute of Forage Crops - Pleven, Bulgaria (2018-19). The highest inhibition effect showed the soil from the rhizosphere zone of Sorghum vulgare var. technicum (17.44) pure grown; alfalfa, grown under cover of Sorghum vulgare var. technicum (14.56) and alfalfa, grown under cover of Sorghum bicolor + Sorghum vulgare var. technicum (16.94). The lowest inhibition effect showed the soil from the alfalfa (6.32), Sorghum sudanense (7.62) both pure grown and alfalfa grown under cover of Sorghum bicolor (7.96). The results obtained indicate that depending on the allelopathic soil activity of Sorghum bicolor, Sorghum sudanense and Sorghum vulgare var. technicum, they can be used for the growing of alfalfa under the cover as a measure for weed control in the year of establishment of the crop and for the increasing the productivity also. The equivalence between the allelopathic soil activity in pure grown crops, assessed by the degree of inhibition in the germination and initial development of Lactuca sativa L. as well as their use as cover crops for alfalfa were found.